Dermal fibroblasts promote cancer cell proliferation and exhibit fibronectin overexpression in early mycosis fungoides. Issue 1 (April 2022) - Beksaç, Burcu; Gleason, Laura; Baik, Sarah; Ringe, John M.; Porcu, Pierluigi; Nikbakht, Neda
Abstract: Background: Mycosis fungoides (MF) is caused by proliferation of malignant T-cells in the skin and may progress to involve blood, lymph nodes, and viscera. While the skin microenvironment is essential for the initiation and progression of MF in early stages, little is known about the impact of skin stroma on the growth and survival of malignant lymphocytes. Objective: We investigated the effect of dermal fibroblasts and their product, fibronectin, on the survival and proliferation of malignant MF cells. Methods: Fibroblasts and malignant MF CD4 T-cells were isolated from skin of patients with early-stage MF. Fibroblast-lymphocyte co-culture experiments and lymphocyte cultures on fibronectin-coated plates were established utilizing the cells derived from lesional skin, blood, and MF cell lines. The survival and proliferation rates of lymphocytes were assessed via Annexin V and carboxyfluorescein succinimidyl ester assays respectively. Additionally, integrin and fibronectin expressions in MF skin were assessed via immunofluorescence. Results: We found that dermal fibroblasts increased the proliferation rates of MF cells, but not normal skin or blood CD4 T-cells. However, fibroblasts did not rescue MF cells from apoptosis in co-cultures. In MF skin, we found an overexpression of a fibronectin isoform not normally found in healthy skin. MF cells expressed fibronectin-binding integrins and adhered to fibronectin but did not exhibit adhesion-mediated survival via fibronectin-integrin interactions. Conclusion: Overall, our results suggest a direct role for fibroblasts, independent of fibronectin-mediated adhesion, in promoting MF cell proliferation. These findings have implications in understanding and targeting the malignant skin stromal microenvironment in cutaneous lymphomas. Highlights: We evaluated the effects of fibroblasts and their product, fibronectin, on mycosis fungoides (MF) cell survival and proliferation using fibroblasts and MF cells directly isolated from patient skin lesions and healthy subjects. Fibroblasts increased MF cell proliferation while suppressing that of normal lymphocytes. Fibroblasts did not rescue MF cells from apoptosis in co-cultures. A fibronectin isoform not normally found in healthy skin was overexpressed in MF skin lesions. MF cells expressed fibronectin-binding integrins and adhered to fibronectin, but their proliferation or survival was not changed when cultured on fibronectin.